Evaluation of outer rotor embedded PMSM using segmented stator - Hairulnizam, Hairul Faizi; Misron, Norhisam; Ibrahim, Nur Amira; Harun @ Ramli, Hafiz Rashidi; Vaithilingam, Chockalingam Aravind; Hanamoto, Tsuyoshi (2024)
To enhance the motor's efficiency, experts prioritize the optimization of the Permanent Magnet Synchronous Motor (PMSM) construction by introducing the consequent-pole (CP) PM rotor which decrease the reliance on PM rotors and decreases the costs by reducing the volume of PM by 30% [1]. Additionally, the external orientation of rotor may have a high torque density, it requires a significant amount of rare-earth PM material. A PM motor with a segmented stator design has the potential to reduce costs, increase flexibility, and minimize windings. Furthermore, the incorporation of a segmented stator can enhance the motor's output torque, elevate both the mean and peak torque, and reduce the cogging torque